Entrepreneurs' gender and financial constraints: evidence from international data - Alexander Muravyev; Dorothea Schäfer; Oleksandr Talavera (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper studies gender discrimination against entrepreneurs by financial institutions. Based on the Business Environment and Enterprise Performance Survey (BEEPS) that covers firms in several countries of Western Europe as well as in the transition countries of Eastern Europe, our analysis suggests that female-managed firms are less likely to obtain a bank loan compared with male-managed counterparts. In addition, there is some evidence that female entrepreneurs are charged higher interest rates when loan applications are approved. Disaggregation of the sample by country groups suggests that these results are driven by firms in the least financially developed countries of the region.
Keywords: G21; J16; L26; 330; entrepreneurship; gender; financial constraints.; Unternehmer; Weibliche Führungskräfte; Verschuldungsrestriktion; Geschlechterdiskriminierung; Europa